Records of Convocation, XX, Index (The Boydell Press, 2006)
The convocation records of the Churches of England and Ireland are the principal source of our information about the administration of those churches from middle ages until modern times. They contain the minutes of clergy synods, the legislation passed by them, tax assessments imposed by the king on the clergy, and accounts of the great debates about religious reformation; they also include records of heresy trials in the fifteenth and sixteenth centuries, many of them connected with the spread of Lollardy. However, they have never before been edited or published in full, and their publication as a complete set of documents provides a valuable resource for scholarship. This volume contains a composite index of source material, references to the Bible, canon law, parliamentary statutes et cetera, and of the subjects discussed and on which legislation has been enacted over the centuries. There is also a complete concordance to David Wilkins' 'Concilia Magnae Britanniae et Hiberniae', much of which has now been replaced by this collection of records